2019
DOI: 10.3390/jcm8122124
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis In Vitro—A Research and Therapeutic Tool in Thalassemia

Abstract: Thalassemia (thal) is a hereditary chronic hemolytic anemia due to a partial or complete deficiency in the production of globin chains, in most cases, α or β, which compose, together with the iron-containing porphyrins (hemes), the hemoglobin molecules in red blood cells (RBC). The major clinical symptom of β-thal is severe chronic anemia—a decrease in RBC number and their hemoglobin content. In spite of the improvement in therapy, thal still severely affects the quality of life of the patients and their famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 89 publications
(101 reference statements)
1
9
0
Order By: Relevance
“…The significant increase in the hematological parameters with Thypa elephantina (TE.AQ) extract, suggest that it may contain phytochemicals that may activate erythropoietin production in the stem cells of experimental animals. Erythropoietin is a glycoprotein hormone which motivates stem cells in the bone marrow to revenue red blood cells (Fibach, 2019). The present study is in agreement with (Oshilonya, IJioma et al, 2015) who reported the effects of Caulis bambusae (Bamboo) stem extract on hematological and biochemical parameters in chinchilla rabbits (Sun, Yu et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The significant increase in the hematological parameters with Thypa elephantina (TE.AQ) extract, suggest that it may contain phytochemicals that may activate erythropoietin production in the stem cells of experimental animals. Erythropoietin is a glycoprotein hormone which motivates stem cells in the bone marrow to revenue red blood cells (Fibach, 2019). The present study is in agreement with (Oshilonya, IJioma et al, 2015) who reported the effects of Caulis bambusae (Bamboo) stem extract on hematological and biochemical parameters in chinchilla rabbits (Sun, Yu et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, human iPSCs have less ethical and social issues compared to human ESCs [24,25]. Human iPSCs are produced by the manipulation of differentiated somatic cells [26][27][28][29]. Reprogramming of human somatic cells through the ectopic expression of transcription factors has provided a new avenue for disease modeling and regenerative medicine [16,30].…”
Section: Introductionmentioning
confidence: 99%
“…1 ). This developmental procedure is controlled by cell-cell/cell-matrix interactions along with several cytokines and growth factors including IL-3, IL-6, erythropoietin (EPO) (the main erythropoietic stimulating hormone), EPO-receptor, members of the transforming growth factor-β (TGF-β), activin A, activin receptor-II, Flt3 ligand (Flt3-L), vascular endothelial growth factor (VEGF), stem cell factor (SCF), thrombopoietin (TPO), and granulocyte colony-stimulating factor (G-CSF) [ 26 , 41 , 42 ]. Erythropoiesis is controlled and characterized via multiple transcriptional regulators, including myb, Sox6, Bcl11A, Gata1, and Klf1 [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation resulted in the identification of a subset of compounds that were ultimately analyzed as Hb inducers on primary cell cultures obtained from β -thalassemia patients. This assay has been widely used to validate the HbF-inducing potential of molecules identified using large or middle-scale screening approaches [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%